1992
DOI: 10.1021/bi00140a023
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of sparsomycin in protein synthesis

Abstract: Before CI isomerizes to C*I, we detect a competitive phase of inhibition (Ki = k5/k4 = 0.05 microM) which eventually, by increasing the concentration of I, becomes linear mixed noncompetitive and involves C*I in place of CI. The equilibration of C and I according to reaction 2 is much slower than the equilibration between C and S in reaction 1 (time-dependent inhibition). The inactivation plots obey reaction 2 and allow us to estimate k6 as equal to 2.2 min-1. The isomerized C*I, free of excess I, can be studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…2 The C5-position of pyrimidines is the location of choice for structural modification because this site is not involved in Watson-Crick base pairing. 3 5-Alkenyluracils have been shown to exhibit antitumor 4 and potent antiviral activities. 5 Structure-activity relationship (SAR) studies demonstrated that the antiviral activity was enhanced when the C5-position was equipped with an unsaturated, E -configured substituent bearing a hydrophobic electronegative functionality (such as an ester) in conjugation with the pyrimidine ring.…”
mentioning
confidence: 99%
“…2 The C5-position of pyrimidines is the location of choice for structural modification because this site is not involved in Watson-Crick base pairing. 3 5-Alkenyluracils have been shown to exhibit antitumor 4 and potent antiviral activities. 5 Structure-activity relationship (SAR) studies demonstrated that the antiviral activity was enhanced when the C5-position was equipped with an unsaturated, E -configured substituent bearing a hydrophobic electronegative functionality (such as an ester) in conjugation with the pyrimidine ring.…”
mentioning
confidence: 99%
“…1), demonstrated suppression of pituitary-ovarian axis in cynomolgus monkeys via chronic oral administration. [12] Other examples include sparsomycin which is an antibiotic and a potential antitumour agent, [13] Zidovudine which is a HIV drug, [14] and Pentothal which is often used as a general anaesthetic [15] (Fig. 1).…”
mentioning
confidence: 99%
“…Ethyl acetate gave the best yield while solvents such as 1,4-dioxane, acetonitrile, and toluene afforded moderate yields of the product. NMP, DMAc, and t-amyl alcohol (t-AmOH) afforded poor results (Table 1, entries [13][14][15][16][17][18][19][20][21][22][23][24].…”
mentioning
confidence: 99%
“…The biological activity resulted from its ability to inhibit the peptide bond-forming step of protein biosynthesis by interacting with the large ribosomal subunit. [7][8][9][10] These potentially important biological activities have made 3 an attractive target for a potential antineoplastic compound. 11) Since thê rst synthetic study of sparsomycin in 1976, 12) synthetic studies of sparsomycin, [13][14][15] total synthesis, [16][17][18] biosynthesis, 19,20) and structure-activity relationship studies [21][22][23][24][25][26][27] have been widely reported.…”
mentioning
confidence: 99%